The Effect of Copper Nanoparticles on Seminal Vesicles and Testosterone Hormone in Male Albino Mice - Mohammed N. Taha (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
The study conducted to demonstrate the effect of copper nanoparticles (Cu-NPs) on the seminal vesicle and testosterone hormone of males' albino mice. Twenty mice were used and divided into four groups control group and three groups that orally administrated with 100 mg/kg Cu-NPs for 7, 14 and 21 days and each group have 5 animals. Then, the blood was withdrawn from the animals to measure the level of the hormone testosterone in the next day after all the dosages period and then the animal was sacrificed. Seminal vesicles isolated from each animal and measured weight then histological sections were prepared to observe the changes of seminal vesicles sections. Then the morphometric was carried out to the lining cells and their nucleus and the thickness of fibro muscular layer surrounding the seminal vesicles. The result showed a significant decrease P <0.05 in the average weights of the seminal vesicles and the testosterone levels of treated animals with Cu-NPs for all three periods compared to the control. At the histological changes levels, the study showed occurrence of atrophy, degeneration of lining cells and pyknotic their nuclei as well as to decline the thickness of the surrounding layer of vesicles. These results were confirmed by morphometric which showed a significant decrease P <0.05 in the average height of lining epithelial cell and the diameter of their nuclei as well as the thickness of the surrounding layer of the vesicle. Depending on the results, this study was approved for the first time that Cu-NPs have negative impact on the effectiveness of the seminal vesicle and testosterone hormone of male albino mice.